Development of Constructivity Learning Model In the Style of To Ugi’ - Subaedah Subaedah (Journal of Research and Multidisciplinary, 2019)
The research aims to develop a Constructivist Learning Model Based on the style of To Ugi (PATU) at Lalabata Elementary School, Tanete Rilau District, Barru District. This type of research is research and development (R & D). The research was carried out by stages: 1) analyzing the level of needs of students towards to ugi-based constructivist learning model (case analysis), 2) designing the development of learning models (research and development), 3) producing to ugi-based constructivist learning model products (in terms of validity, practicality, effectiveness). Data analysis used quantitative qualitative descriptive with SPSS program. The results of the study show: 1) the analysis of the level of needs of students towards to ugi-based constructivist learning model 'is really needed in improving the character of students considering the shifting moral values are very alarming, 2) the design of the learning model development consists of: syntax = 3.77 (very valid), supporting theory = 3.6 (very valid), Social System = 3.68 (very valid), Reaction System (teacher behavior) = 3.78 (very valid), Supporting System = 3.35 (valid), Instructional Impact and Companion Impact = 3.67 (very valid), Learning Implementation = 3.6 (very valid), Learning Environment and Management Tasks = 3.75 (very valid), Evaluation = 3.55 (very valid). The results of the PATUl model design analysis value ∑ = 3.64 can be said that PATU’ model has VERY VALID criteria. The results of the trial analysis